Designing clinical trials for combination immunotherapy: a framework for glioblastoma - Singh, Kirit; Batich, Kristen A.; Wen, Patrick Y.; Tan, Aaron C.; Bagley, Stephen J.; Lim, Michael; Platten, Michael; Colman, Howard; Ashley, David M.; Chang, Susan M.; Rahman, Rifaquat; Galanis, Evanthia; et al. (Clinical cancer research, 2022)
Immunotherapy has revolutionized treatment for many hard-to-treat cancers but has yet to produce significant improvement in outcomes for patients with glioblastoma. This reflects the multiple and unique mechanisms of immune evasion and escape in this highly heterogeneous tumor. Glioblastoma engenders profound local and systemic immunosuppression and is remarkably effective at inducing T-cell dysfunction, posing a challenge to any immunotherapy-based approach. To overcome these mechanisms, multiple disparate modes of immune-oriented therapy will be required. However, designing trials that can evaluate these combinatorial approaches requires careful consideration. In this review, we explore the immunotherapy resistance mechanisms that have been encountered to date and how combinatorial approaches may address these. We also describe the unique aspects of trial design in both preclinical and clinical settings and consider endpoints and markers of response best suited for an intervention involving multiple agents.